La Lucha Continua: A Presentist Lens on Social Protest in Ecuador - Schwab, Julia; Justus Liebig University Giessen (My University, 2023)
Ecuador has one of the most progressive constitutions in Latin America. It defines the state as plurinational and guarantees collective rights to Indigenous people and even to Nature itself. At the same time, the oil sector has been of strategic importance and “national interest” to both right- and left-wing governments for the last decades, contributing with its rents and revenues to around one-third of the state coffers. Therefore, the extractivist model remains unchallenged and still promises development - while reproducing systemic inequalities and a “continuum of violence.” In June 2022, the Indigenous movement called for a nationwide strike to draw attention to the socio-economic crisis following the pandemic. The authorities harshly repressed the mobilization and a racializing media discourse demarcated the “Indigenous” agenda from the needs of “all Ecuadorians,” classifying the protesters as “terrorists” and thus, a threat to the nation. Drawing on ethnographic research, this article discusses the role of extractivism in social mobilization. Exploring the future of social protest in Ecuador in the face of new pressures like climate change and the energy transition, it argues that extractivist patterns will change globally and amplify social discontent and mobilization.
Keywords: Amazon; climate change; CONAIE; energy transitio; extractivism; Indigenous movement; rentier society; violence; ddc:300; ddc:320; ddc:333.7